Strategi Meningkatkan Daya Saing Organisasi Melalui Pendekatan Manajemen Perubahan Kolaboratif Di Erick Minimarket Lubeg - Firdaus, Firdaus; Angraini, Anggi; Mulani, Maylan; Delfira, Wina; Putra, Ramdani Bayu (CV. ITTC INDONESIA, 2024)
The purpose of this study is to examine how information technology and organizational change management can be used to support business sustainability in MSMEs in Padang City. To face today's business competition, the role of information technology and organizational change management is very important, because information technology functions as a manager of information available at that time. Change management provides a structured approach to assist individuals in an organization in transitioning from their current state to their desired state. Organizational change management is concerned with identifying groups and individuals who must change. Not only that, organizational change management requires the development of a specific plan to successfully implement change. The main purpose of change management is to prepare for a smooth and successful transition.